A Social Norms and Identity Approach to Increasing Fruit and Vegetable Intake of Undergraduate Students in the United Kingdom - Fischera, Wanda; van Beusekom, Mara; Higgs, Suzanne; Cecil, Joanne E. (Frontiers in Psychology, 2022)
This study investigated the influence of descriptive norm messages that either communicated that university students eat a sufficient amount of fruit and vegetable (F&V) or that they do not, on F&V consumption, and whether or not any effects are moderated by student identification. An online 2 (Norm: “Sufficient”/“Insufficient”) × 2 (Identification: “Low”/“High”) experimental design was employed. Infographics containing “sufficient”/“insufficient” F&V intake descriptive norms were presented. An identification manipulation was employed to create “high”/“low” student identifiers. F&V intake intentions were assessed after the manipulations; self-reported F&V intake was reported at 2 days post-intervention. Undergraduate students in the United Kingdom (N = 180) reported their intake intentions, of which 112 (62%) completed the behavioral follow-up. Participants were predominantly white female students from Scottish universities, mean age 20.4 (±1.6) years. Baseline mean F&V consumption was high (4.5 ± 2.8). There were no significant main effects of Norm or Identification manipulations on F&V intentions and intake. Significant norm × identification interactions were revealed for fruit intake intentions and vegetable intake at follow-up, indicating half-portion differences ( 40 g) between groups. Ironic effects were observed for “high” identifiers, who neither intended to, nor acted in accordance with group norms; “low” student identifiers intended to and followed group norms, whereby the “sufficient”/“low” group intended to consume significantly more fruit portions and consumed more vegetables than the “insufficient”/“low” group. Given the half-portion differences between groups resulting from the norm × identification interactions, future research on a larger sample of young adults with low F&V intake is warranted to further explore the conditions under which moderating effects of identification are observed and the underlying mechanisms.